Alice's adventures in Wonderland ; Through the looking-glass, and what Alice found there - Carroll, Lewis, 1832-1898.; Tenniel, John, 1820-1914.; Carroll, Lewis, 1832-1898. (New York : Smithmark, 1995)
By falling down a rabbit hole and stepping through a mirror, Alice experiences unusual adventures with a variety of nonsensical characters.
Alice's adventures in Wonderland originally published 1865; Through the looking-glass first published 1871.
Keywords: Alice -- (Fictitious character from Carroll) -- Fiction